Intelligent control for improving the quality of fresh meat products with rich lipid in cold chain logistics: research status, challenge, and potential applications - Yingqiu Luo; Min Zhang; Qi Yu; Arun S. Mujumdar; Luming Rui (Critical Reviews in Food Science and Nutrition, 2025)

FishMambaNet: A Mamba-Based Vision Model for Detecting Fish Diseases in Aquaculture - Zhijie Luo; Rui Chen; Shaoxin Li; Jianhua Zheng; Jianjun Guo (Fishes, 2025)
The growth of aquaculture poses significant challenges for disease management, impacting economic sustainability and global food security. Traditional diagnostics are slow and require expertise, while current deep learning models, including CNNs and Transformers, face a trade-off between capturing global symptom context and maintaining computational efficiency. This paper introduces FishMambaNet, a novel framework that integrates selective state space models (SSMs) with convolutional networks for accurate and efficient fish disease diagnosis. FishMambaNet features two core components: the Fish Disease Detection State Space block (FSBlock), which models long-range symptom dependencies via SSMs while preserving local details with gated convolutions, and the Multi-Scale Convolutional Attention (MSCA) mechanism, which enriches multi-scale feature representation with low computational cost. Experiments demonstrate state-of-the-art performance, with FishMambaNet achieving a mean Average Precision at 50% Intersection over Union (mAP@50) of 86.7% using only 4.3 M parameters and 10.7 GFLOPs, significantly surpassing models like YOLOv8-m and RT-DETR. This work establishes a new paradigm for lightweight, powerful disease detection in aquaculture, offering a practical solution for real-time deployment in resource-constrained environments.

From rolling-in to enveloping: An active gripper for efficient handling of spherical fruits in agriculture - Huanhuan Qin; Zicheng Qiu; Haoran Zhu; Rui Diao; Fengwei Che; Xingjian Gu; Yan Luo; Baohua Zhang; Mingzhou Lu (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Dynamic response and liquefaction mitigation of immersed tunnels under seismic loads: A coupled seawater-seabed-tunnel analysis - Weiyun Chen; Zhiqiang Luo; Lingyu Xu; Yewei Zheng; Lei Su; Rui Huang (Soil Dynamics and Earthquake Engineering, 2025)

900 Wh L–1 lithium-ion batteries enabled by self-assembled copolymer induced built-in electric field on graphite anode - Yumeng Zhao; Changdong Li; Dehua Xu; Rui Li; Bin Han; Xinlian Chen; Bohua Wen; Haimei Xie; Aoxuan Wang; Jiayan Luo (Science Bulletin, 2025)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

The efficient removal of dolomite from phosphate ores using a novel collector: Flotation selectivity and collecting mechanism - Yifan Zhang; Yudi Yan; Bingqiao Yang; Rui Ma; Yang Xu; Huihua Luo; Fang Zhou (Minerals Engineering, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Effects of sun drying combined with baking processes on the flavor quality of Chongqing Tuocha raw tea - Hongyu Luo; Rui Chang; Shanmin Chen; Yueyun Liu; Yi Wang; Linying Yuan; Juan Yang; Ying Zhang; Ruiqi Duan; Quan Wu; Yingfu Zhong (Food Chemistry, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Optimized preparation of dredged sediment-based functional ceramsite: thermodynamic profiling and formation mechanism - Yuqi Luo; Yan Wang; Yongqiang Ma; Jie Wang; Rui Deng; Chen Li; Zhengbo Yue; Xiaomoli Li; Xinyuan Zhan (Environmental Research, 2025)

Integrated untargeted metabolomics and physiological analysis reveal the response mechanisms of Procambarus clarkii larvae to carbonate alkalinity exposure - Kun Guo; Zhigang Zhao; Rui Zhang; Liang Luo; Shihui Wang; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Spatiotemporally controlled intelligent hydrogel platform for precision RNA interference therapy in lumbar facet joint osteoarthritis - Chongzhi Pan; Shuihua Ding; Linfeng He; Xiang Luo; Le Liao; Jian Zhang; Rui Ding; Peichuan Xu; Huajun Pan; Xinxin Miao; Xigao Cheng (Chemical Engineering Journal, 2025)

Synergistic lattice engineering and surface passivation via cerium modification for robust ultrahigh-nickel layered oxide cathodes - Lunhao Deng; Rui Zhou; Jie Chen; Xiaotian Xu; Yuanyuan Chen; Xinyu Zhao; Liang Luo; Wang Xiang; Xiangwan Lai; Yingjie Zhang; Xianshu Wang; Ding Wang; et al. (Chemical Engineering Journal, 2025)

One polymer–multiple functions: Waterborne dual dynamic polyacrylate networks for self-healing and recyclable adhesives and coatings - Yu Chen; Wang Li; Rui Pu; Fengbiao Chen; Yujun Cheng; Yao Liu; Dong Luo; Siyu Nie; Xuelang Gao; Liang Shen; Fei Gao (Chemical Engineering Journal, 2025)

Electric field-biochar integrated anammox system for high-efficiency nitrogen and phosphorus removal under elevated nitrogen concentration shock - Rui Hu; Xue Chen; Wanjiang Li; Yule Han; Shiliang Heng; Jiayi Wang; Yijing Gao; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Chemical Engineering Journal, 2025)

Low-temperature microwave pyrolysis PVC to achieve modulation of elemental chlorine migration and conversion: performance evaluation of microwave absorption-catalysis-chlorine fixation trifunctional catalyst - Wenjun Fu; Juan Luo; Shichang Shun; Jiangyi Luo; Chengling Liu; Rui Ma (Chemical Engineering Journal, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Hdac11 inhibits apoptosis in zebrafish cells under cold stress via downregulating pdcd6 through its downstream enhancer - Mingzhi Ma; Juntao Luo; Xin Li; Rui Deng; Hui Jiang; Bingshe Han; Junfang Zhang (Molecular Biology Reports, 2025)

Effect of Manure Application on Few Soil Properties and Crop Yield Under Greenhouse Cultivation-a Comprehensive Analysis - You Wu; Jiale Zhang; Wei Si; Rui Liu; Zhenxin Qiu; Jianhua Yang; Renlei Luo; Xin Lei; Weiqi Wang; Musa Ma; Xinhao Yang; Cheng Yang (Journal of Soil Science and Plant Nutrition, 2025)

PGC1α alleviates M1 macrophage polarization through dual regulation of succinate metabolism and TRAF5 expression to mitigate TLR4/NF-κB-driven inflammatory cascades and myocardial ischemia/reperfusion injury - Jiajie Leng; Zhenrui Cao; Letai Li; Dingheng Hu; Yuxiang Luo; Bin Tu; Xiaoying Cao; Rui Tao; Yingjiu Jiang; Hongtao Tie (Inflammation Research, 2025)

MZB1-Driven Endoplasmic reticulum stress model as a predictor of breast cancer progression and survival - Purong Zhang; Rui Wang; Yuying Wang; Ning Zhang; Ke Luo (Functional & Integrative Genomics, 2025)

How to achieve sustainable development of smart city: a comprehensive bibliometric analysis - Xizi Luo; Rui Huang (Clean Technologies and Environmental Policy, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Leaf-herbivory induced trade-off: Aboveground defense sacrifices root flavonoids to enrich microbes for dual resistance - Junxing Zhang; Chen Ye; Lifen Luo; Yingwei Su; Chenjing Zhao; Yanyan He; Wenjie Luan; Tingshu Yang; Rui Zhang; Bin Chen; Min Yang; Shusheng Zhu (Agriculture, Ecosystems & Environment, 2025)

The impacts of agricultural intensification and diet diversity on solitary bee exposure to heavy metals - Xiaoyu Shi; Michael Orr; Williamson Gustave; Changsheng Ma; Shanlin Liu; Qingsong Zhou; Mei Wang; Fang Ouyang; Douglas Chesters; Rui Cheng; Chaodong Zhu; Arong Luo (Agriculture, Ecosystems & Environment, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Effect of production and environment factors on the migration and conversion of cyclolinopeptides in linseed (Linum usitatissimum L.) oil - Tingting Guo; Luyao Xie; Yan Luo; Qianchun Deng; Rui Liu; Chuyun Wan (Food Chemistry, 2025)

Enhanced effects of species richness on cadmium phytoextraction across eastern China: A meta-analysis - Rufeng Guo; Xianzhen Luo; Li Zhou; Rui Zhang; Lingling Zhang; Yuanwen Kuang; Biao Qiu; Dazhi Wen (Environmental Research, 2025)

Joint associations of air pollution and frailty on cardiovascular diseases and the modifying role of physical activity: Evidence from the CHARLS - Ying-Yuan Gan; Yun-Dan Luo; Lu Zhai; Qian Liao; Rong-Rui Huo (Environmental Pollution, 2025)

Dynamic response of ceramic-reinforced metallic corrugated sandwich structures under combined blast-fragment loading - Chang-ye Ni; Cong Luo; Lu-sheng Qiang; Xin-yi Bai; Jia-le Wu; Jian-hong Zhang; Rui Zhang (Engineering Structures, 2025)

Surrogate model construction and improved detection of rail corrugation in high-speed railways based on a hybrid neural network - Rui Ouyang; Jun Luo; Shengyang Zhu; Mei Chen; Wanming Zhai (Engineering Structures, 2025)

Chlorine atoms modulated Fe d-band centers drive non-radical pathways to degrade bisphenol A with attenuated intermediates toxicity - Jianwen Huang; Yuxin Liu; Kun Yao; Qintie Lin; Zirui Zhao; Jieyi Pan; Longyi Wei; Hao Luo; Rui He (Chemical Engineering Journal, 2025)

UV-switchable dual-mode sensing in a lead-free CsCu2I3 perovskite sensor for selective detection of mixed amines - Rui Wu; Qingyi Guan; Mingji Xu; Ruixiang Li; Shu Chen; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Novel laser-driven fast pyrolysis of biomass: Insights into biochar characteristics and applications - Rui Ma; Jintao Luo; Xiaoning Duan; Yuwan Sheng; Shaohui Wang; Deli Zhang; Fang Wang; Shuo Yang; Weiming Yi (Bioresource Technology, 2025)

Human influence on summer wetting in Northwest China from 1961 to 2014: Roles of greenhouse gases and anthropogenic aerosols - Rui He; Yan Guo; Buwen Dong; Neng Luo; Zihui Zhao; Zhibo Gao (Atmospheric Research, 2025)

Harnessing synthetic microbial communities for sustainable agriculture: Enhancing soil health and crop yields - Yunhe Cui; Yue Tao; Yang Luo; Rui Sun; Siyue Han; Yang Yang; Zhongmin Dai; Ying Zhang (Critical Reviews in Environmental Science and Technology, 2025)

Multi-objective optimization of pressure in self-pressurized irrigation networks based on meta-heuristic algorithm with valve openings - Qinggang Liu; Zhenhua Wang; Jinzhu Zhang; Ningning Liu; Rui Chen; Pengcheng Luo (Computers and Electronics in Agriculture, 2025)

Planning smart link-based geofences for urban sustainability via speed limit management - Wenqi Lu; Dongyu Luo; Ziwei Yi; Yikang Rui; Bin Ran (Transportation Research Part D: Transport and Environment, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Hybrid artificial bee colony algorithm with Q-learning for distributed heterogeneous flexible job shop scheduling problem considering machine preventive maintenance - Rui Wu; Enzhuang Luo; Xixing Li; Hongtao Tang; Yibing Li (Swarm and Evolutionary Computation, 2025)

Inspecting urban transit-oriented development from the perspective of human activity: A case study of Xi'an, China - Jiayu Liu; Xiping Yang; Lin Luo; Junyi Li; Hongfei Chen; Rui An; Jiyuan Li (Journal of Transport Geography, 2025)

Spatial prediction of soil cadmium concentration: A multi-model prediction system with novel evaluation metrics - Ziqian Zhong; Qihong Zhu; Xinliang Liu; Shufang Pan; Lei Luo; Hanhua Zhu; Rui Liu; Daoyou Huang (Journal of Hazardous Materials, 2025)

Mechanistic insights into Perfluorooctanoic acid (PFOA) and Perfluorooctane sulfonates (PFOS)-induced nitrification acceleration: Interkingdom collaboration of AOA-comammox in calcareous soils - Shuoshuo Wu; Keyi Zhang; Yuehang Zhu; Luo Zhang; Wangying Ding; Jun Li; Baowei Hu; Guixin Chu; Rui Tao (Journal of Hazardous Materials, 2025)

Photocatalytic biorefining green closed-loop: Photocatalytic alkali lignin depolymerization in supramolecular solvent - Chengcheng Suo; Xiaochang Zhang; Xinai Li; Jifang Zhang; Hongru Zhang; Rui Teng; Wei Li; Sha Luo; Bing Tian; Qingjiang Pan; Chunhui Ma; Zhijun Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Impact of amplicon length on the identification of edible oils based on real-time PCR - Kai Chen; Bin Xiao; JianZhi Luo; XueWei Yuan; Juan Zhang; Songxue Wang; Rui Zhang; Nan Wang; LiQiang Liu; AiKe Li; Ailiang Chen (Food Control, 2025)

Effects of re-enter water on antioxidant, immune, intestinal flora and metabolome of Chinese mitten crab (Eriocheir sinensis) after high temperature air exposure - Xiangyi Deng; Yuhong Yang; Zhiqiang Li; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Self-adhesive cellulose nanofibers achieve ultra-high flame retardancy via deep eutectic solvent mediated dual P/S functionalization - Xiaoqi Yang; Jing Zhou; Muyao Zhang; Yujia Luo; Haiyang Lu; Linghui Qi; Yue Ni; Changlei Xia; Jianzhang Li; Rui Yang (Chemical Engineering Journal, 2025)

Multifunctional N, S-co-doped carbon quantum dots enable defect healing and conductive network construction in spent LiFePO4 cathodes - Juyong Wang; Bingqiang Tan; Dezhi Chen; Xianfu Liu; Rui Zhou; Chongwen Hu; Chunli Liu; Guisheng Zeng; Xubiao Luo (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

A novel method for predicting debris flow hazard: a multi-strategy fusion approach based on the light gradient boosting machine framework - Tianlong Wang; Qi Ge; Tianxing Ma; Hao Chen; Rui Luo; Xu Wang; Keying Zhang; Zhaowei Chu; Xiaohui Ni; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Zinc and manganese impact on cabbage (Brassica rapa) cadmium tolerance: comparative transcriptomic and metabolomic study - Wanyu Li; Fanxin Qin; Banglin Luo; Qiu Huang; Anqi Xu; Rui Wu (Plant and Soil, 2025)

BDNF Alleviates Noise-Induced Cochlear Synaptopathy Through Inhibition of Autophagy - Fei Wang; Qianru Yu; Yangtuo Luo; Rui Guo; Liyuan Wu; Xinyu Song; Yang Li; Shuna Li; Ke Liu; Xuejun Jiang (Molecular Neurobiology, 2025)

Hawthorn Polysaccharide Enhances Growth, Immunity, and Intestinal Health in Crucian Carp (Carassius auratus) Challenged with Aeromonas hydrophila - Liang Luo; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Cheng Zhao; Baoquan He; Wei Wang; Wenhua Wu (Fishes, 2025)
Bacterial disease infections pose a major challenge to the healthy growth of crucian carp. Hawthorn polysaccharide (HP) is a natural active ingredient in hawthorn and has a wide range of pharmacological effects. However, the mechanism of HP against Aeromonas hydrophila infection in crucian carp cultures is unknown. In this study, it was found that 0.4% HP could significantly reduce the mortality of crucian carp, significantly increase the activities of T-AOC, SOD, CAT, and GSH-PX of crucian carp infected with A. hydrophila (p

Formation Control of Multiple UUVs Based on GRU-KF with Communication Packet Loss - Juan Li; Rui Luo; Honghan Zhang; Zhenyang Tian (Journal of Marine Science and Engineering, 2025)
In response to the problem of decreased collaborative control performance in underwater unmanned vehicles (UUVs) with communication packet loss, a GRU-KF method for multi-UUV control that integrates a gated recurrent unit (GRU) and a Kalman filter (KF) is proposed. First, a UUV feedback linearization model and a current model are established, and a multi-UUV controller-based leader–follower method is designed, using a neural network-based radial basis function (RBF) to counteract the uncertainty effects in the model. For scenarios involving packet loss in multi-UUV collaborative communication, the GRU network extracts historical temporal features to enhance the system’s adaptability to communication uncertainties, while the KF performs state estimation and error correction. The simulation results show that, compared to compensation by the GRU network, the proposed method significantly reduces the jitter level and convergence time of errors, enabling the formation to exhibit good robustness and accuracy in communication packet loss scenarios.

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Efficient solar-driven tandem catalysis for biomass valorization: selective C C bond cleavage to synthesize xylitol - Liangdong Hu; Huiyan Zhang; Zupeng Chen; Nengchao Luo; Lian-Hua Xu; Kai Wu; Longfei Hong; Sheng Chu; Rui Xiao (Science Bulletin, 2025)

Crustal deformation characteristics and tectonic implications on the northeastern margin of the Tibetan Plateau - MengYa Li; HuaJian Yao; JiKun Feng; XianWei Zeng; GuoFu Luo; ChenXi Wang; Rui Ma (Physics of the Earth and Planetary Interiors, 2025)

Barn swallow (Hirundo rustica) transfers current-use pesticides from agricultural fields to houses - Jiahe Zeng; Ziqing Luo; Kaiying Guo; Li Tian; Rui Zhang; Xiaobo Zheng (Environmental Pollution, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Template synthesized spider network-like conjugated microporous polymers composite membranes with high mechanical properties for separation and flexible wearable devices - Yong Zhang; Wenwen Luo; Zhentao Hu; Hanxue Sun; Zhaoqi Zhu; Jiyan Li; Rui Jiao; An Li (Chemical Engineering Journal, 2025)

BaTiO3 dressed in carbon multifunctional layer achieving high areal capacity zinc metal batteries - Rui Wang; Jing Xu; Shijun Luo; Yan Guo; Baohe Yuan; Lei Xu; Junming Li; Yongqi Zhang; Yusheng Wang; Wenpeng Yang; Jinbing Cheng; Yongsong Luo (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

A SERS aptasensor based on Au@Ag bimetallic nanostars-magnetic covalent organic composites for rHuEPO-α detection - Na Zhou; Yu Zeng; Qiuwen Huang; Rui Tan; Yushi Chen; Liu Zhong; Xiaojun Luo; Xiaojun Deng (Analytica Chimica Acta, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Resilience-based restoration sequence optimization of disrupted transportation networks: A novel matheuristic approach - Xinhao Cui; Bo Li; Siyue Zhang; Ziguang Ji; Shitao Wang; Rui Luo; Yi Ren; Yiyong Xiao (Transportation Research Part D: Transport and Environment, 2025)

Leaching salinity and mulching straws during freeze-thaw period enhance post-thawing cotton yield and quality by optimizing soil aggregates stability - Pengcheng Luo; Lu Zhao; Rui Chen; Pengpeng Chen; Yam Prasad Dhital; Haiqiang Li; Dongwang Wang; Juanjuan Yang; Yu Chen; Qinggang Liu; Zhenhua Wang (Soil and Tillage Research, 2025)

3D inversion of airborne transient electromagnetic data using deep learning - Shuowei Zhang; Rui Liu; Hao Feng; Zhihong Wang; Shangbin Liu; Yan Luo; Ziqiang Zheng; Huaifeng Sun (Journal of Applied Geophysics, 2025)

Construction and analysis of atmospheric visibility and fog-haze datasets in China (2001−2023) based on machine learning models - Haifeng Xu; Wenhui Luo; Jinji Ma; Bing Dong; Cheng Wan; Shijie Zhao; Cheng Dai; Rui Qian; Zhengqiang Li (Atmospheric Research, 2025)

Unveiling anomalies in visual processing regions in obsessive-compulsive disorder: evidence from gray matter volume and functional connectivity analyses - Rui Liu; Fengxia Zhang; Pengchong Wang; Jia Luo; Yue Liu; Kaiyin Huang; Xiangyun Yang; Aihong Yu; Zhanjiang Li (Brain Imaging and Behavior, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

The efficient separation of apatite and dolomite using sodium dextran sulphate as an eco-friendly depressant: Flotation performances and atom-scale interaction mechanism - Rui Ma; Bingqiao Yang; Bing Deng; Hui Shao; Yimei Xiao; Huihua Luo (Minerals Engineering, 2025)

Controllable synthesis of bimetallic Cu-Zn conjugated polymer microflowers with splendid laccase- and antioxidase-like activities for colorimetric detection of organic pollutants and eliminating cigarette smoke radicals - Shu-Chang Zhao; Dan Wu; Ya-Nan Kong; Jing-Jing Luo; Bo-Yi Yuan; Rui-Lin Liu (Journal of Hazardous Materials, 2025)

Multidimensional analysis of sensory perception and neurophysiological responses to marinated beef cooked by diverse methods - Tianyi Yang; Wei Jiang; Chencheng Luo; Jin Hu; Wei Xu; Peng Zhang; Xiaofei Jin; Yuxuan Zhou; Rui Liu; Zhiyu Qian; Yamin Yang (Innovative Food Science & Emerging Technologies, 2025)

Multifunctional amine salt additive for enhancing the performance of perovskite and perovskite/silicon tandem solar cells - Jun Qu; Wenfeng Zhang; Yangdi Chen; Huiyao Zhao; Yanbei Wei; Rui Zhou; Hongjie Wan; Jie Deng; Dongyong Fan; Yuchen Luo; Haijin Li (Chemical Engineering Journal, 2025)

Reduced serum levels of mitochondria-derived peptide MOTS-c in patients with obstructive sleep apnea - Zhuoding Luo; Rui Ji; Renjing Ye; Yawen Shi; Qingfeng Pang; Min Yin (Sleep and Biological Rhythms, 2025)

Inversion of Stress Redistribution Based on Focal Mechanism Solutions: A Case Study of the Dongtan Coal Mine - Kai Zhan; Hao Luo; Rui Xu; Xiaotao Wen; Cong Wang (Rock Mechanics and Rock Engineering, 2025)

How Does Climate Change Influence the Regional Ecological–Social Risks of Harmful Dinoflagellates? A Predictive Study of China's Coastal Waters - Shangke Su; Zhaohe Luo; Jianhua Kang; Xinyuan Guo; Changyou Wang; Rui Jin; Jianguo Du; Xinqing Zheng; Kieng Soon Hii; Shifeng Fu; Wenjia Hu; Bin Chen (Global Change Biology, 2025)
Harmful dinoflagellates are widely distributed in coastal waters worldwide, posing multiple ecological and socioeconomic threats. Climate change may alter the biogeography of these species; however, few studies have linked shifts in harmful dinoflagellates' ecological distribution to their socioeconomic impacts. This study developed a framework to assess the spatiotemporal ecological–social risks posed by harmful dinoflagellates, identifying these algae as risk sources and considering mariculture and coastal populations as the primary risk receptors. China is the world's largest mariculture producer, with approximately 600 million residents living in coastal areas. Focusing on 14 key harmful dinoflagellate species in Chinese coastal waters, we evaluated ecological–social risks under present conditions and two projected climate scenarios for 2100. Our findings indicate that climate change may lead to reductions in suitable habitats for harmful dinoflagellates in tropical and subtropical regions, while habitats in higher‐latitude areas are likely to remain stable or expand. Risk area expansion is projected for four species and increased average risk intensity for three, with two species experiencing both. Nationally, total risk area is projected to remain stable, while cumulative risk intensity may decline by 16.64%. Regionally, risk intensity is expected to rise in northern provinces (up to 30.46%) and decline across most southern provinces. Importantly, we reveal a potential spatial “decoupling” of risk sources and receptors along the coast of China in the future. This decoupling demonstrates a reduced overlap between harmful dinoflagellate distributions and areas with dense mariculture or populations. Our findings suggest that, contrary to the common assumption that climate change universally exacerbates harmful algal impacts, these effects may vary across regions and species, highlighting the importance of localized adaptation strategies in risk assessment. This study provides a robust tool for understanding harmful dinoflagellate risks under climate change, thereby supporting the sustainable management of coastal ecosystems.

Archean to early Mesoproterozoic crustal evolution of the Yangtze Craton: Insights from U-Pb-Hf-O isotopic and trace elemental compositions of detrital zircon - Xinyu Cai; Rui Li; Guangyan Zhou; Heng Luo; Zhifu Liu; Nimat Ullah Khattak; Wei Wang (Precambrian Research, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

New luminescence chronology of a loess-paleosol sequence at Jinchuan and its implications for aeolian deposition processes in the Tibetan Plateau - Shengli Yang; Li Liu; Dongxue Li; Rui Li; Weiming Liu; Yuanlong Luo; Pushuang Li; Jinbo Zan; Xiaomin Fang (Geomorphology, 2025)

Terpene-conjugated curcumin analogs alleviated alcoholic liver injury in rats through mitigation of intestinal barrier abnormalities - Shuaihu Tao; Ruanping Song; Ziyu Wang; Wenjing Xie; Siyuan Xiao; Yangyang Liao; Xinjie Zhang; Qiongdan Hu; Xinxing Tang; Jingyuan Huang; Wan Liao; Hongtao Xiao; et al. (Food Bioscience, 2025)

Unveiling the potential supply of cultural ecosystem services on the Qinghai-Tibet Plateau: Insights from tourist hiking trajectories - Sheng Huang; Jiawei Yi; Yunyan Du; Fuyuan Liang; Rui Xu; Nan Wang; Jiale Qian; Wenna Tu; Peixian Luo; Andrew Z.F. Xing (Ecosystem Services, 2025)

A new CNN-GRU deep learning framework optimized by CHIO for precise prediction of debris flow velocity - Liangxu Shen; Tianxing Ma; Hao Chen; Bingfeng Ye; Rui Luo; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

A promising mutant strain of Pyropia haitanensis ZD-2 for floating cultivation with enhanced growth, holdfast strength, and desiccation tolerance - Yujie Wang; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Journal of Applied Phycology, 2025)

Camellia nitidissima Chi extract ameliorates dextran sulfate sodium-induced acute ulcerative colitis in mice by inhibiting TLR4/NF-κB-mediated inflammatory activation - Lirong Li; Rui Huang; Wenwen Li; Dengjie Yao; Beibei Zhang; Mengna Li; Shunan Luo; Yu Qin; Wenwen Zhang (Inflammopharmacology, 2025)

Mesoscopic interpretation of fines clogging-induced permeability changes in completely decomposed granite - Rui Chen; Zhi-yuan Luo; Ai-guo Li; Hao Wang; Lei-lei Liu; Liang-liang Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Effects of dietary Lycium barbarum polysaccharide on the growth, antioxidant, immunity response, and intestinal microbiota in Bulatmai barbel (Luciobarbus capito) - Liang Luo; Xianwei Meng; Shihui Wang; Rui Zhang; Kun Guo; Wei Xu; Wei Wang; Zhigang Zhao (Animal Feed Science and Technology, 2025)

Analysis of the Relationship Between Organic Acid, Total Soluble Solids, Total Phenolic, and Total Flavonoids in Ficus carica - Jiajie Luo; Xueqian Dong; Jing Liang; Ming Jia; Lei Sun; Yanling Han; Siduo Zhou; Rui Sun (Applied Fruit Science, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

The antioxidant protein PntA coordinates with OmpW to resist oxidant stress in Actinobacillus pleuropneumoniae - Weiyao Han; Qiuhong Zhang; Zhen Luo; Hao Tang; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Impact of the drying process on the flavor characteristics of two economically important laver species, Pyropia haitanensis and Neopyropia yezoensis - Yuting Zhang; Juanjuan Chen; Yongbo Huang; Qijun Luo; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Food Chemistry, 2025)

Silver carp by-product hydrolysate: A promising mucin substitute for stimulating Akkermansia muciniphila growth and metabolic activity - Huijuan Zhang; Rui Zhang; Shengjun Chen; Ruifang Feng; Sam K.C. Chang; Yongkang Luo; Hui Hong; Yuqing Tan (Food Bioscience, 2025)

Spatiotemporal evolution and risk thresholds of PM2.5 components in China from the human health perspective - Haifeng Xu; Wenhui Luo; Cheng Dai; Shijie Zhao; Rui Qian; Bing Dong; Zhengqiang Li; Jinji Ma (Environmental Pollution, 2025)

A novel large linear stroke high-static-low-dynamic stiffness vibration isolator with high magnetic negative stiffness and compactness - Wuhui Pan; Hongyu Xie; Pengfei Ai; Rui Liu; Bo Gao; Shilin Xie; Yajun Luo; Yahong Zhang (Engineering Structures, 2025)

Lightweight, compressible and superhydrophobic coal-based nanofibrous/graphene oxide composite aerogel towards efficient oil and organic solvents adsorption - Yanchun Pei; Xueyan Wu; Zhichao Ren; Yan Lv; Rui Xue; Xin Luo; Jixi Guo; Dianzeng Jia (Desalination, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

3D DNA walkers integrated with self-reporting MOFs: Pioneering ratiometric electrochemical sensing for Staphylococcus aureus - Xianzhu Meng; Rui Ma; Xiao Luo; Yang Liu; Xiaoli Yin; Huiwen Gu; Ying Chen (Analytica Chimica Acta, 2025)

TadpoleTraits : A Global Database on Morphological Traits of Tadpoles of Anura - Yanfang Song; Rui Tian; Yongle Wang; Pingfan Wei; Tao Zhang; Shuaiwei Luo; Zhiyong Yuan; Weiwei Zhou (Global Ecology and Biogeography, 2025)
Motivation Functional diversity is an important dimension of biodiversity. In animals, most species have complex life cycles, such that the same species can display great differences in traits and ecological roles across different life history stages. Consequently, the patterns and driving factors of functional diversity can vary considerably among the different life stages. However, research on stages other than adults is rare, with data scarcity being a potential reason. The order Anura of Amphibia is a highly diverse group of terrestrial vertebrates, comprising more than 7800 species. Anurans have complex life cycles, and our knowledge about functional traits of the larval stage is extremely limited. To fill this gap, we collected morphological traits of tadpoles globally and compiled a database covering 1993 species to facilitate future studies. This database can help us gain a more comprehensive understanding of anuran biodiversity. Additionally, it offers a valuable tool for testing ecological and evolutionary hypotheses related to complex life cycles in animals. Main Types of Variables Contained Twenty‐three traits collected from literature and 11 traits obtained by image measuring. Spatial Location and Grain Global. Major Taxa and Level of Measurement Anura, species. Software Format xlsx.

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Biochar-supported Fe₃O₄ nanoparticles affects bacterial community diversity and phosphorus speciation transformation during pig manure aerobic composting by generating hydroxyl radicals and hydrogen peroxide - Ning Yuan; Kang Wang; Jia Zhou; Nana Luo; Rui Yu (Journal of Environmental Chemical Engineering, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

P2/O3 biphasic Fe/Mn based cathodes for simultaneously realizing kinetic-enhancement and air-stabilization - Rui Huang; Shaohua Luo; Qi Sun; Lixiong Qian; Xin Liu; Shengxue Yan (Chemical Engineering Journal, 2025)

A stable and high-contrast color/fluorescence dual-mode stimuli-responsive poly (imino sulfone) for anti-counterfeiting and encryption - Tengning Ma; Hong Luo; Weiyuan Zhou; Huijuan Zhang; Rui Yuan; Qing He; Ying Huang; Li Yang; Guanjun Chang (Chemical Engineering Journal, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Glaesserella parasuis induces tissue transglutaminase-mediated fibrinogen crosslinking through NF-κB activation - Bin Ma; Yanxi Wan; Ran Zhuo; Huimin Gong; Yuan Gao; Rui Luo; Xueying Hu; Kexin Hua; Yuncai Xiao; Hui Jin (Veterinary Microbiology, 2025)

Environmental factors ultraviolet a and ozone exacerbate the repeated inhalation toxicity of 6PPD in mice via accelerating the aging reaction - Xianjie Li; Caixia Wu; Ping Yang; Yanxi Li; Shuai Wang; Dan Cai; Ran Wei; Jinfeng Gao; Xuemei Wen; Jieping Luo; Rui Wang; Xueyuan Bai; et al. (Journal of Hazardous Materials, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

Performance of electro-assisted ecological floating bed in antibiotics and conventional pollutants degradation: Mechanisms and microbial response - Liangjing Zhang; Yan Luo; Shucong Lv; Yunlong Liu; Rui Wang; Yu Wang; Kuixuan Lin; Lusan Liu (Journal of Environmental Management, 2025)

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Experimental and numerical investigation on a novel dual-stage friction self-centering damper - Yong Yang; Jianyang Xue; Zheng Luo; Rui Liu (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Zearalenone delays tissue regeneration by dysregulating neutrophil balance in zebrafish (Danio rerio) larvae - Rui Luo; Bo Wang; Rui Luo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Uncovering the charge storage mechanism of anti-perovskite nitrides Co3InN cathode materials in alkaline aqueous electrolytes - Yuming He; Rui Ding; Yi Li; Jian Guo; Yiqing Lu; Ziyang Yan; Zhiqiang Chen; Jiajie Luo (Chemical Engineering Journal, 2025)

Highly stretchable, conductive, and self-adhesive starch-based hydrogel for high-performance flexible electronic devices - Rui Chen; Lei Wang; Dan Ji; Mengqing Luo; Zihao Zhang; Guiyan Zhao; Xiaohua Chang; Yutian Zhu (Carbohydrate Polymers, 2025)

Metabolome analysis reveals the involvement of oxylipins in regulating the maturation of conchosporangia in Pyropia haitanensis - Yi Liu; Haike Qian; Shanshan Zhu; Tingting Niu; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Algal Research, 2025)

Wheat Fusarium head blight severity grading using generative adversarial networks and semi-supervised segmentation - Guoqing Feng; Ying Gu; Cheng Wang; Dongyan Zhang; Rui Xu; Zhanwang Zhu; Bin Luo (Computers and Electronics in Agriculture, 2025)

Assessment of the bioflocculant production and safety properties of Metabacillus hrfriensis sp. nov. based on phenotypic and whole-genome sequencing analysis - Rui Zhang; Zhigang Zhao; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Aquaculture, 2025)

Temperature-induced pathogen Vibrio fortis NH-2 triggers bleaching and rough-shell disease in Porphyra sensu lato - Xuxu Luo; Yangying Mao; Qiqin Liu; Yepengyu Gu; Haimin Chen; Juanjuan Chen; Qijun Luo; Rui Yang (Aquaculture, 2025)

Corrigendum to “Antiviral effects of duck type I and type III interferons against Duck Tembusu virus in vitro and in vivo” [Vet. Microbiol. 287 (2023) 109889] - Peng Zhou; Dejian Liu; Qingxiang Zhang; Wanrong Wu; Dong Chen; Rui Luo (Veterinary Microbiology, 2025)

Antagonistic activity of Pochonia chlamydosporia against three helminth eggs and characterization of its serine protease - Luyao Hao; Fengmiao Zhao; Yuan Guo; Yuan Ma; Zhengyi Li; Wen Wang; Hongliang Luo; Rui Wang (Veterinary Parasitology, 2025)

First investigation of the luminescence dating of loess in the eastern Tibetan Plateau using K-feldspar MAR MET-pIRIR protocol - Li Liu; Shengli Yang; Pushuang Li; Jingzhao Zhang; Rui Li; Dongxue Li; Xuechao Xu; Yuanlong Luo; Xiuyun Yang (Quaternary Geochronology, 2025)

Revealing the relationship between 2D/3D built environment and jobs-housing separation coupling nonlinearity and spatial nonstationarity - Rui An; Zhaomin Tong; Bo Tan; Qiangqiang Xiong; Yuanyuan Luo; Yaolin Liu; Linchuan Yang; Xiping Yang (Journal of Transport Geography, 2025)

Microplastic effects on soil nitrogen cycling enzymes: A global meta-analysis of environmental and edaphic factors - Yangzhou Xiang; Bin Yao; Josep Peñuelas; Jordi Sardans; Luca Nizzetto; Rui Li; Ying Liu; Yang Luo; Mari Räty; Jian Long; Yuan Li (Journal of Hazardous Materials, 2025)

Transboundary cooperation potential under climate change and hydropower development in the Dulong-Irrawaddy river basin: A perspective on the water-energy-food-ecosystem nexus - Ziyue Xu; Kai Ma; Jiwei Leng; Kaiwen Zhang; Rui Luo; Daming He (Journal of Cleaner Production, 2025)

Efficient removal of cationic malachite green using co-pyrolyzed corn straw biochar-montmorillonite composites - Xiaodong Yang; Zhiyong Hou; Xuefei Yang; Minghui Li; Yuanxia Guo; Kai Wang; Shuaiqi Luo; Jin Zhao; Pengkai Sun; Qiang Yang; Rui Chen; Yan Yan; et al. (Journal of Environmental Management, 2025)

Deciphering the coupling of anoxic/aerobic and sulfur autotrophic denitrification: Performance, antibiotic resistance genes, and microbial community structure - Yang He; Zhigang Wang; Cheng Luo; Xin Li; Zhaoqi Wang; Aslan Temirkhanov; Zhadyrassyn Nurbekova; Zhouliang Tan; Sayan Zhangazin; Rui Wang; Yangwu Chen (Journal of Environmental Chemical Engineering, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

Study on the synergistic effect of co-pyrolysis gasification of low-grade non-cohesive coal and waste biomass - Xiaowei Gan; Zhengjie Chen; Wenhui Ma; Rui Xie; Pen Luo (Fuel, 2025)

Experimental study of deformation evolution around the gas extraction borehole in a composite stratum - Chunhui Cheng; Qianting Hu; Yongjiang Luo; Baocai Wang; Rui Tao; Yongliang Sun (Fuel, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

UPLC-HDMS revealed numerous novel compounds in soybean crude oil - Zhaohui Sun; Feng Dong; Rui Zhang; Xinyu Song; Xiaocai Huang; Yingran Dong; Xiaofei Jia; Shunian Luo; Ying Li; Maoqing Wang (Food Chemistry, 2025)

Gradient ethanol extracts of Coreopsis tinctoria buds: Chemical and in vitro fermentation characteristics - Shang Gao; Tiantian Li; Zhao-Rong Li; Bingwu Liao; Mouming Zhao; Chunxia Zhou; Donghui Luo; Rui-Bo Jia (Food Chemistry, 2025)

A wearable electrochemical sensor utilizing multifunctional hydrogel for antifouling ascorbic acid quantification in sweat - Zhen Wei; Yanxin Li; Shuyue Guo; Rui Han; Xiliang Luo (Analytica Chimica Acta, 2025)

The extensive cultivation of Pyropia haitanensis along the coastal areas influences the ecological dynamics of nearby intertidal mudflat pond water - Peihao Liu; Qijun Luo; Shanshan Zhu; Juanjuan Chen; Rui Yang; Tingting Niu; Tiegan Wang; Peng Zhang; Haimin Chen (Frontiers in Marine Science, 2025)
Introduction The aquaculture in intertidal mudflat ponds on the coast of the East China Sea typically coexists with oceanic seaweed cultivation in the nearby open water area, forming an interconnected aquatic ecosystem. This study aimed to understand the impact of the seaweed cultivation on the water quality and microbial communities in their neighboring intertidal mudflat ponds. Methods A unique recirculating culture system was established, integrating seaweed farming in marine areas with aquaculture ponds on mudflats, and incorporating an effluent treatment process for added efficiency. Water samples were collected from three sites, including open water areas with or without seaweed ( Pyropia haitanensis ) cultivation, the aquaculture mudflat ponds, and effluent water ponds, with control sites for comparison. The dynamic diversity patterns and structure of microbial communities were determined by 16S and 18S rRNA sequencing, and the environmental factors were measured. Results In the offshore aquaculture area, the cultivation of P. haitanensis increased the dissolved oxygen and pH, decreased inorganic nutrients, reduced the alpha diversity of bacteria, established the dominance of Proteobacteria, but did not influence the composition of microeukaryotes. These changes in the seawater subsequently affected the dynamics in the corresponding aquaculture ponds, where the water quality was improved, the microbial diversity was enhanced, and the abundance of functional bacteria such as Microbacteriaceae was increased. According to the co-occurrence network analysis, the cultivation of P. haitanensis potentially improved the stability of the microbial communities in both the offshore aquaculture area and the onshore aquaculture ponds and allowed them to resist stress better. In addition, after the effluent from the aquaculture ponds was purified in the treatment ponds with mangroves and oysters, the water quality improved and the abundances of Dinophyceae and Bacillariophyta decreased. Discussion This study highlights the positive effects of P. haitanensis cultivation on water quality and microbial stability in adjacent aquaculture ponds.

Sustainability assessment of station-city integration based on DPSIR-SDGs framework: a case study of Chengdu in China - Zhenhua Luo; Zijing Chen; Xingling Wu; Haize Pan; Fanglin Wang; Rui Tu; Zujun Yao; Yue Wang; Shenjie Chen (Environment, Development and Sustainability, 2025)

Optimizing urban car-sharing systems based on geospatial big data and machine learning: A spatio-temporal rebalancing perspective - He Li; Qiaoling Luo; Rui Li (Travel Behaviour and Society, 2025)

To kill or to piggyback: Switching of viral lysis-lysogeny strategies depending on host dynamics - Chen Hu; Xiaowei Chen; Wei Wei; Douglas Wallace; Jihua Liu; Yao Zhang; Lianbao Zhang; Dapeng Xu; John Batt; Xilin Xiao; Qiang Shi; Qiang Zheng; et al. (Science of The Total Environment, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

KOH-modified biochar enhances nitrogen metabolism of the chloroquine phosphate-disturbed anammox: Physical binding, EPS modulation and versatile metabolic hierarchy - Rui Hu; Xue Chen; Yule Han; Wanjiang Li; Shuting Zhang; Zhaobin Liu; Jiandong Wang; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Journal of Hazardous Materials, 2025)

Enhanced CO2 capture performance of N, S co-doped biochar prepared by microwave pyrolysis: Synergistic modulation of microporous structure and functional groups - Jiashan Chen; Junhao Lin; Juan Luo; Zhen Tian; Junshen Zhang; Shichang Sun; Yonglin Shen; Rui Ma (Fuel, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Fatigue behavior of square steel strut-to-gusset plate welded connections under eccentric compression: Full-scale and reduced-scale tests - Xiaoqing Xu; Hongfa Luo; Bin Wang; Yuqing Liu; Kaixiang Miao; Rui Hao; Weiwei Lin; Yuwen Zhou; Dongyang He; Md Asadujjaman (Engineering Structures, 2025)

A prediction model of the optimal defrosting initiating time for the air source heat pumps with different configurations and operations - Shiquan Wang; Wenzhe Wei; Jianfei Luo; Wei Wang; Yuying Sun; Zhaoyang Li; Chengyang Huang; Rui Tang; Shiming Deng (Energy and Buildings, 2025)

Effects of water immersion on immune, intestinal flora and metabolome of Chinese mitten crab (Eriocheir sinensis) after air exposure - Xiangyi Deng; Zhiqiang Li; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Guo Qiao; Yuhong Yang; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Water-triggered stimuli-responsive luminescent crown-ether-coordinated cuprous bromides for multi-functional applications - Rui Wu; Hao Yang; Meifeng Jiang; Hui Tong; Xinyu Hu; Ziyang Liu; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Synchronously enhanced breakdown strength and energy storage ability of cellulose acetate flexible films via introducing ultra-low content of carbonized polymer dots - Rui Luo; Fan Zhang; Jing-hui Yang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2025)

Secular evolution of continental crust of the North China Craton constrained by U-Pb and Lu-Hf-O/Sm-Nd isotopic analyses of detrital zircon and monazite in river sediments - Guangyan Zhou; D. Graham Pearson; Yan Luo; Long Li; Christopher M. Fisher; Rui Li; Wei Wang; Yuanbao Wu (Chemical Geology, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

17α-methyltestosterone induced hepatocyte apoptosis through endoplasmic reticulum stress in Takifugu fasciatus - Xuanyin Chen; Sheng Luo; Yanfang Li; Rui Li; Xiaojun Li; Zhengyang Hu; Shaowu Yin; Tao Wang (Journal of Oceanology and Limnology, 2025)

Influence of land-use type on earthworm diversity and distribution in Yunnan: Insights from soil properties - Chang-E Liu; Qing-Rui Luo; Yan-Lan Xiao; Hong-Yang Li; Hong-Juan Dong; Chang-Qun Duan (Applied Soil Ecology, 2025)